STUDY OF SILICON NANOWIRE GROWTH ON Ag CATALYST USING HWC-IN PLASMA-VHF-PECVD THROUGH PRESSURE OPTIMIZATION - ANGGORO (NIM : 20210301); Pembimbing Prof. Toto Winata, Ph.D, DIKY
Development of nanotechnology like nanowire is still growing rapidly and has become a very interesting research topic. Research on silikon nanowire (SiNW) growth has been performed by using plasma enhanced chemical vapour deposition (PECVD). Before the silicon nanowire grown by PECVD method, metal nanocluster as a catalytic coating on the substrate is required to grow SiNW using this method. Nanocatalys layer is one of the determinants of size the diameter silicon nanowire growth structure. The catalyst used is metallic silver (Ag). Selection of silver as a catalyst for silver based on its electrical and thermal conductivity which are better among all metals. The use of silver in the study nanokatalis capped at 0025 grams. Nanocatalys silver in the deposition on glass substrates by evaporation in a vacuum to form a thin film on a substrate Ag. Having produced a thin layer of silver on a substrate made annealing at a temperature of 400oC during one hour to repair nanocatalyst structure and form small islands of nanometer-sized, until affecting the structure of the silicon nanowire. Ther esults nanocatalyst growth characterization by SEM and EDX results in metallic silver-annealing for one hour produces Ag islands 30-110 nm sized and Ag composition at 2.78%. Ag that are annealed for one hour and then used for silicon nanowire growth. As the carrier gas used SiH4 silane gas with silica precursor flow rate 70 sccm and rf power of 8 watts. Variations in pressure parameters optimization is done at 100, 200, 300 and 400 mTorr. SEM, EDX, and X-RD performed to characterize the silicon nanowire. From the results of SEM and EDX, deposition pressure of 100 mTorr to produce silicon nanowire with a high ratio. Diameter silicon nanowire obtained 70-120 nm and a length of silicon nanowire 200-5000 nm. While the results of EDX showed the percentage of silver around 2.42%. With the results obtained low pressure (100 mTorr) and low power (8 watts) to produce silicon nanowire better.